Metabolism of BYZX in Human Liver Microsomes and Cytosol: Identification of the Metabolites and Metabolic Pathways of BYZX - Yu, Lushan; Jiang, Yan; Wang, Lu; Sheng, Rong; Hu, Yongzhou; Zeng, Su (PLOS ONE, 2013)
BYZX, [(E)-2-(4-((diethylamino)methyl)benzylidene)-5,6-dimethoxy-2,3-dihydroinden-one], belongs to a series of novel acetylcholinesterase inhibitors and has been synthesized as a new chemical entity for the treatment of Alzheimer’s disease symptoms. When incubated with human liver microsomes (HLMs), BYZX was rapidly transformed into its metabolites M1, M2, and M3. The chemical structures of these metabolites were identified using liquid chromatography tandem mass spectrometry and nuclear magnetic resonance, which indicated that M1 was an N-desethylated and C = C hydrogenation metabolite of BYZX. M2 and M3 were 2 precursor metabolites, which resulted from the hydrogenation and desethylation of BYZX, respectively. Further studies with chemical inhibitors and human recombinant cytochrome P450s (CYPs), and correlation studies were performed. The results indicated that the N-desethylation of BYZX and M2 was mediated by CYP3A4 and CYP2C8. The reduced form of β-nicotinamide adenine dinucleotide 2′-phosphate was involved in the hydrogenation of BYZX and M3, and this reaction occurred in the HLMs and in the human liver cytosol. The hydrogenation reaction was not inhibited by any chemical inhibitors of CYPs, but it was significantly inhibited by some substrates of α,β-ketoalkene C = C reductases and their inhibitors such as benzylideneacetone, dicoumarol, and indomethacin. Our results suggest that α,β-ketoalkene C = C reductases may play a role in the hydrogenation reaction, but this issue requires further clarification.